MODAL SOSIAL KELOMPOK TANI TERNAK DI DESA BULUH RAMPAI KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU (STUDI PADA KELOMPOK TANI TERNAK ENGGAL JAYA) - Diah Nisita Rugmi; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was carried out on the Enggal Jaya Farmer group in the village of Buluh Rampai Seberida district Indragiri Hulu district. The formulation of the problem discussed in the study is to find out the elements of social capital that play a role in the activities of Enggal Jaya livestock farmer groups. The theory used is the theory of social capital which consists of network, trust, and norms. This type of research uses a descriptive qualitative approach. The research subjects were six people, namely the chairman, secretary, treasure, member of the Enggal Jaya livestock farming group, field extension officers and organic fertilizer buyers. Informan determination technique using purposive sampling technique. the results of this study are that social capital plays an important role in groups or organizations. Elements of social capital that play a role in the activities of the Enggal Jaya livestock farmer group, the most prominent of which is trust among fellow members by lending each other money to group members in need. And the weak element of social capital in the network in marketing organic fertilizer so that the scope in marketing the results of processing cow manure into organic fertilizer is still in the surrounding area and norm social. Keywords: Social Capital, Farm, group